Generalization of gronwall-bellman and beekhary lemmas - Kasjanov, V. (Proceedings of National Aviation University (archive), 2001)
Well known lemmas touching useful integral inequalities for positive functions may be generalized. This paper contains some generalized lemmas similar to the Gronwall-Bellman and Beekhary lemmas